1995
DOI: 10.1021/j100038a004
|View full text |Cite
|
Sign up to set email alerts
|

An Oriented Cluster Formation of Endohedral Y@C82 Metallofullerenes on Clean Surfaces

Abstract: An oriented head-to-tail cluster formation of an endohedral yttrium metallofullerene, Y@c82, on a Cu( 11 1) 1 x 1 clean surface has been observed directly by the use of a scanning tunneling microscopy (STM) under ultrahighvacuum conditions. The STM observation reveals that the Y@c82 molecules preferentially form dimers and one-dimensional clusters at the step edge of the Cu ( 1 1 1) surface. The observed intermolecular distance (1 1.2 f 0.5 A) is smaller than that of the simple Y@c82---Y@& van der Waals distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 3 publications
1
40
1
Order By: Relevance
“…In contrast to the trimer domination in our observation, the cluster size distribution has a maximum at dimer in the case of Y@C 82 adsorbed on Cu͑111͒ surface. 10 We believe that such a difference is caused by the different nature of the substrates used and, as a result, the different intermolecular interaction. In our experiment, the Nd@C 82 molecules are adsorbed on a C 60 film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the trimer domination in our observation, the cluster size distribution has a maximum at dimer in the case of Y@C 82 adsorbed on Cu͑111͒ surface. 10 We believe that such a difference is caused by the different nature of the substrates used and, as a result, the different intermolecular interaction. In our experiment, the Nd@C 82 molecules are adsorbed on a C 60 film.…”
Section: Resultsmentioning
confidence: 99%
“…9 The same conclusion was reached also on the basis of scanning tunneling microscopy ͑STM͒ studies, which showed a nearly spherical shape for Y@C 82 and Nd@C 82 molecules. 10,11 People also have found evidence that the metal atom donates three electrons to the carbon cage. [12][13][14][15] For example, the synchrotron x-ray diffraction experiment on a powder Y@C 82 sample revealed the presence of such a charge transfer from the analysis of the total electron density distribution of an Y@C 82 microcrystal.…”
Section: Introductionmentioning
confidence: 99%
“…Y@C 82 molecules have been imaged on Cu͑111͒ with STM and shown to preferably adsorb at substrate terrace edges, indicating that isolated molecules have significant mobility. 8,9 A common feature of fullerene absorption on noble-metal surfaces is the ionic character of the bonding, which arises from charge transfer from the substrate to the fullerene. This leads to the expectation that the electronic and structural properties of endofullerenes in monolayer films will be different from bulk properties.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on a variety of M@C 82 species have provided strong evidence that the metal atoms are located inside the cage but off its center. [6][7][8][9][10][11][12] For M@C 82 it is assumed that, as a result of complexation, two or more electrons are transferred from the metal atom to the carbon cage, leading to a Coulomb interaction between both. 10,13 As a result, M@C 82 compounds comprising a variety of lanthanide atoms are predicted to have quite large dipole moments.…”
Section: Introductionmentioning
confidence: 99%
“…10,13 As a result, M@C 82 compounds comprising a variety of lanthanide atoms are predicted to have quite large dipole moments. 13,14 However, although structural probes have recently provided unequivocal evidence for the existence 11,12 of permanent moments, their magnitudes still have to be determined experimentally.…”
Section: Introductionmentioning
confidence: 99%